Xerostomia yang diinduksi obat pada Pasien dengan gangguan kecemasan : Laporan Kasus - Rinawati Satrio; Arsa Hadiyatama W.A.; Agatha Tunggadewi P.; Wisnu Riyadi (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
Saliva plays an important role in oral health because it helps taste, protects the mucosa and teeth, and aids the digestive process. Low salivary flow is known as xerostomia. Xerostomia is caused by various factors, one of which is the consumption of certain types of drugs such as drugs in patients with anxiety disorders. The purpose of writing this journal is to report cases of xerostomia experienced by patients with anxiety disorders. A male patient came with complaints of dry oral mucosa and discomfort for chewing, swallowing, and speaking. The patient is undergoing treatment for an anxiety disorder and is taking the drugs diazepam, fluoxetine, alprazolam, and clozapine. Measurement of the patient's salivary flow rate showed results of 0.8 ml/minute when stimulated and 0.1 ml/minute without stimulation. Patients with anxiety disorders who have to take antidepressant drugs for a long time are advised to maintain oral hygiene so that they can improve their quality of life.